A Turner syndrome case associated with anal atresia, interrupted aortic arch and multicystic dysplastic kidney - Mutlu, Mehmet; Dilber, Embiya; Aslan, Yakup; Okten, Ayşenur; Oztürk, Osman (The Turkish Journal of Pediatrics, 2010)
Although renal and cardiac malformations are commonly seen in Turner syndrome (TS), anorectal malformations, multicystic dysplastic kidney and interrupted aortic arch are quite rare in TS. A newborn with TS with three quite rare congenital malformations (imperforate anus/anal atresia associated with rectovestibular fistula, interrupted aortic arch, and multicystic dysplastic kidney) is presented.